2021
DOI: 10.12688/f1000research.28450.1
|View full text |Cite
|
Sign up to set email alerts
|

Defining and validating regenerative farm systems using a composite of ranked agricultural practices

Abstract: Background: Ongoing efforts attempt to define farms as regenerative to aid marketers, policymakers, farmers, etc. The approach needs to balance precision with function, and must be transparent, simple, scalable, transferable, incorruptible, and replicable. Methods: We developed practice-based scoring systems to distinguish regenerative cropland and rangeland, and validate them based on whether these scores scaled with regenerative goals on actual farm operations. Study systems included cornfields of the Upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…The treatments were defined by rankings derived from a character matrix of nine different practices that were considered as regenerative or conventional (Table 1) (LaCanne and Lundgren, 2018;Fenster et al, 2021). Engaging in a regenerative practice or abstaining from a conventional practice resulted in the farm receiving a score of 1 for that matrix category.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The treatments were defined by rankings derived from a character matrix of nine different practices that were considered as regenerative or conventional (Table 1) (LaCanne and Lundgren, 2018;Fenster et al, 2021). Engaging in a regenerative practice or abstaining from a conventional practice resulted in the farm receiving a score of 1 for that matrix category.…”
Section: Methodsmentioning
confidence: 99%
“…A minimum of five regenerative practices was used as the regenerative threshold for two reasons. First, there are five principles underlying regenerative agricultural systems: minimizing soil disturbance, eliminating or reducing agrichemical use, eliminating spatio-temporal bare soil events, maximizing plant diversity, and integrating livestock into a cropping operation (Rodale, 1983;Rhodes, 2017;LaCanne and Lundgren, 2018;Gosnell et al, 2019;Pecenka and Lundgren, 2019;Fenster et al, 2021). Furthermore, in Fenster et al (2021) it was found that in cropland systems, farms separated into two distinct clusters based on their regenerative score.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations